Health service providers' perspectives on the influence of modern health systems on adolescents' sexual health practices in Umguza and Mberengwa districts of Zimbabwe - Wilfred Njabulo Nunu; Lufuno Makhado; Jabu Tsakani Mabunda; Rachel Tsakani Lebese (BMC, 2022)
Plain English language Health service providers play a significant role in crafting and implementing health policies and programs that manage adolescent sexual health-related matters. Different strategies have been implemented in different country settings to improve adolescents sexual health-related outcomes. The role played by health service providers is not adequately documented to aid decision making in policy formulation and implementation. This work explores and documents the roles that modern health systems play through the specified health service provider in managing adolescent sexual health issues. The study also examines the potential for integrating modern health systems with indigenous health systems to improve adolescent sexual health matters. The study further presents ways of overcoming challenges that could derail the possible integration of the two mentioned health systems in the management of adolescent sexual health-related matters.